Heart failure following oncological treatment - Marangou, J.; Redfern, A.; Haddad, T.; Rankin, J.; Dwivedi, Girish (2018)
© 2018 Wolters Kluwer Health, Inc. All rights reserved. Purpose of review The aim of this review is to give the reader an up-to-date overview of the progress made in the burgeoning field of cardio-oncology, encompassing oncological treatments conferring risk, prediction strategies to identify patients at risk, imaging and biomarker monitoring for emergent or subclinical toxicity and prevention in primary and secondary settings with a focus on heart failure. Recent findings The rapid recent advances in cancer management, particularly with the expansion of targeted and immunotherapies, have led to substantial improvements in outcome, but have also added to the potential causes of cardiac toxicity, which can lead to heart failure. Against this, there has been progression in the field of imaging for cardiac toxicity, identification of at-risk individuals and the clarification of the role of therapy for prevention and treatment of cardiac toxicity. Summary The findings described in this review provide guidance to clinicians in order to direct monitoring strategy and therapy choice, both in the individual with preexisting cardiac comorbidities and in those predicted to be at the highest risk of cardiac toxicity wherever therapy elements carrying cardiac risk are considered oncologically appropriate.